Distribution, assessment and coupling relationship of heavy metals and macroinvertebrates in sediments of the Weihe River Basin. (October 2019) - Wang, Xinxin; Su, Ping; Lin, Qidong; Song, Jinxi; Sun, Haotian; Cheng, Dandong; Wang, Shaoqing; Peng, Jianglin; Fu, Jiaxu
Highlights: Investigating the distribution of heavy metals and macroinvertebrates in sediments of Weihe River Basin. Assessing the sediment environment quality based on multiple assessment indices. Identifying suitable bioindicators to monitor heavy metal pollution in sediments. Abstract: In order to evaluate the distribution of heavy metals and macroinvertebrates and to clarify the coupling relationship between them, a total of 54 samples of the 0–10 cm layer and 10–20 cm layer sediments were collected from 27 sites in the Weihe River Basin. Geo-accumulation index, Ecological potential risk index, Pollution load index, and Consensus-based sediment quality guidelines were employed to evaluate the ecological risk associated with heavy metals in sediments. Macroinvertebrate community structure was analyzed, following which the quality surrounding habitat was evaluated basing on the indexes. Our results confirmed that the orders of pollution level were 10–20 cm >0–10 cm at different layers and Cd > Ni > Pb > Cu > Cr > Zn for different metals. Through correlation analysis and redundancy analysis, macroinvertebrate metrics exhibited significant correlations with heavy metals. Gastropods and R (Ratio of Ephemeroptera and Trichoptera index to Chironomidae) were selected as bioindicators in overall qualitative analysis. In the 0–10 cm layer, Gastropods and Family biotic index could be selected as bioindicators. Whereas, in the 10–20 cm layer, suitable bioindicators were Oligochaetes and DM (Maralef richness index). Heavy metals, especially Cd, in sediments may pose adverse impact on macroinvertebrate community.